Disparities in Health and Oral Health Behaviors Among Adolescents from Multicultural Families in South Korea - Seon-Hui Kwak PhD; Deuk-Sang Ma PhD (Inquiry: The Journal of Health Care Organization, Provision, and Financing)
This study analyzed changes over time in order to identify disparities in health and oral health behaviors among adolescents from multicultural families residing in Korea. This was a cross-sectional analysis of secondary data utilizing raw data from 2011 to 2022 from the Korea Youth Risk Behavior Survey, a statistical dataset provided by the Korea Disease Control and Prevention Agency. The variables included demographic characteristics, socioeconomic characteristics, health behavior (diet, alcohol consumption, smoking), and oral health behavior (toothbrushing behavior, preventive care behavior, oral symptom experience, and school-based oral health education experience). In comparison to non-multicultural adolescents, multicultural adolescents were more likely to perceive their oral health behavior as unhealthy and less likely to engage in toothbrushing after lunch. In addition, multicultural adolescents had higher rates of soda intake and smoking experience than non-multicultural adolescents. During the period between 2011 and 2022, multicultural adolescents had less experience of dental sealants and scaling than non-multicultural adolescents. The disparities in health status and oral health behavior between the 2 groups persisted over a 12-year period. It was necessary to develop active interventions to reduce health and oral health disparities between multicultural and non-multicultural adolescents.